Presence of Herpesviridae Genome in CSF of GBS Patients (Bangladesh Journal of Neuroscience, 2018)
Background: Guillain Barre Syndrome (GBS) is considered as an immune mediated inflammatory disease of peripheral nerves and nerve roots. Herpes viruses like CMV, EBV, HSV and VZV infections are associated with GBS. The aim of the study was to identify the presence and frequency of different Herpes virus genome by PCR assay in CSF of GBS patientsMethods: An observational, cross sectional study was carried out in the Department of Neurology, BSMMU, and Dhaka. A total 50 (fifty) admitted GBS patients were included after fulfilling the inclusion and exclusion criteria. About 2 ml of CSF was taken for detection of viral nucleic of CMV, EBV, HSV1, HSV2, VZV and HHV6 by Multiplex PCR method.Results: Herpesviridae genome in CSF of study population was present in 9 (18%) patients. Maximum 3 (33.3%) cases were HSV1, EBV and HSV2 found in 2 (22.2%) patients, CMV and VZV in 1 (11.1%) patient respectively. AMAN (66.6%) was the most frequent electrophysiological pattern; followed by AIDP (33.3%), mean CSF protein was (159±81) mg/dl and mean cell count was (2±3)/cmm in these patients. Herpes virus genome positive group patients were more disabled and received definitive treatment more than the others.Conclusion: Herpesviridae genome was present in CSF of GBS especially in early collected CSF sample. Antiviral drugs might have a role in treating GBS patients having Herpes virus genome in CSF.Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 39-44